Contemporary Development Of Creative Industries In Bosnia And Herzegovina - Nurković, Rahman (Quaestiones Geographicae, 2015)
The article consists of three basic parts. In the first, the concept of post-socialist urban settlements and the position of creative industries in them are presented. In the second, examples of the development of creative actions of cities are given. In the third, the role of local policy in the development of new creative industries in Bosnia and Herzegovina is critically analysed, emphasising some of its shortcomings and drawing up recommendations for future policy measures. In Bosnia and Herzegovina, contemporary ideas of the development of the creative industries started to develop at the end of 2001 with the use of the technology of the developed countries of the world.